A case for agent-based models in organizational behavior and team research. Issue 1 (9th March 2015) - Secchi, Davide
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims at introducing agent-based models (ABMs) and reviews some of their features in an attempt to show why they can be useful for organizational behavior research. Design/methodology/approach – The use of simulations has increased substantially in the past ten to fifteen years, but management seems to hold back to the agent-based "revolution". The paper first describes the ABMs, and then discusses some of the issues that usually prevent management scholars from using simulations. Findings – This paper indicates how an agent-based approach can help overcome the hesitations surrounding computer simulations because (a) it makes it relatively easy to model emergent and complex social phenomena, and (b) simulation is made easier by user-friendly software platforms that connect it to the existing research methods. Originality/value – This article describes ABMs in a way that may be attractive to organization scholars, and it depicts the frontiers of a more flexible computational and mathematical approach to organizations, management and teams.